Islamic ethics: An outline of its concept and essence (II) - Hashi, Abdurezak Abdulahi (IIUM Press, 2016)
Since the early epochs of the Muslim history, the study of ethics, a field that is traditionally known among Muslim scholars as tahdhib al-akhlaq (character purification), has been an essential part of Muslim intellectual heritage. It is true that the Qur’an and Sunnah are the foundations of good morals, to which Muslims, including companions of the Prophet (s. a. w.), made constant reference to address moral issues. However, Muslim theologians and jurists (fuqaha) as well as the Sufis (ahl al-tasawuf), gave a considerable effort, time and again, to address, though in different approaches, the nature, the scope and the parameters of the Islamic ethics. This paper uses analytical method, and it aims to highlight the essence of the Islamic ethics. It provides an explanatory account of the basic components of the Islamic moral system, such as the inborn character (fitrah), the good motive (niyyah hassanah) of the moral agent and the role of the shari’ah principles in determining the moral property of given moral conducts. The related texts of the Qur’an and Prophetic narrations as well as the opinion of the scholars in this topic would be analysed.